The State of Continuous Assessment Practices in Junior Secondary Schools in Kenema City (Global Journal of Human-Social Science, 2018)
The study investigated Continuous Assessment Practices in Junior Secondary Schools in Kenema City Three research objectives guided the study Responsibilities of teachers in continuous assessment practices Aspects of Child s Development Educational Objectives assessed rated and School Resources Facilities available and used The population comprised of all Junior Secondary Schools in Kenema city and a sample size of ten Junior Secondary schools was randomly selected Questionnaire Observation and interview were the main instruments used to collect data Data were analyzed using simple percentages tables bar charts and pie charts Results indicated that teachers had responsibilities such as subject teacher class teacher Continuous Assessment Record CAR teacher and guidance counsellor The Cognitive aspect is assessed rated by all the teachers while the Affective and Psychomotor aspects are assessed by class teachers only School resources facilities were available were not adequate and also not used by teachers and pupils during teaching and learning activities Recommendations include The Ministry of Education Science and Technology should provide appropriate and adequate school facilities and finance schools to undertake workshops seminars and in-service courses on Continuous Assessment Practices The principals should ensure that all teachers are involved in assessing rating of the Cognitive Affective and Psychomotor aspects of child s development
Keywords: assessment practices; cognitive; continuous assessment; school facilities